Evaluation and Performance of Activated Sludge Hi-Kleen Treatment Plant (ASHTP): A Case Study - Wakimin, Nur Diana; Idris, Juferi; Francis, Lydia Dundun; Neging, Maureen; Muskil, Siti Rafiqah; Marusin, Harzuinda; Suhaimi, Nik Nur Dania Farahin Nik Mohamed; Husen, Rafidah; Ajien, Azrine (Journal of Asian Scientific Research, 2021)
Pollutants from sewage wastewater are major concerns due to their environmental effects. Thus, an effective sewage wastewater treatment plant is important to ensure discharged effluent is well treated before it can be released to rivers or water streams. This study aims to evaluate the performance of the Activated Sludge Hi-Kleen Treatment Plant (ASHTP) located at H Block (ASHTP at H Block) and L Block (ASHTP at L Block) in UiTM Sarawak Branch, Samarahan Campus, Sarawak, Malaysia. The evaluation was based on physicochemical and removal efficiency namely pH, temperature, turbidity, chemical oxygen demand (COD), and total suspended solids (TSS) from raw influent and treated effluent. The findings indicated that the overall performance of both ASHTP at H Block and L Block were satisfactory where treated effluent meets the standard discharge limits of Environmental Quality (Sewage) Regulations 2009 (Standard B). For ASHTP at H Block, the removal efficiencies of turbidity, COD, and TSS were found to be 86.00, 13.76, and 88.02% respectively, in which the pH, temperature, turbidity, COD, and TSS of the treated effluent were 7.30, 28.10°C, 10.40 NTU, 14.10 mg/L and 8.90 mg/L respectively. Meanwhile, for ASHTP at L Block, the removal efficiencies of turbidity, COD, and TSS were found to be 43.20, 41.90, and 51.61% respectively, in which the pH, temperature, turbidity, COD, and TSS in the treated effluent were 7.30, 27.90°C, 21.10 NTU, 58.10 mg/L and 18.00 mg/L respectively. Proper maintenance of sewage treatment plant is important to ensure its effectiveness as well as to prolong its lifespan.